ANALISIS PERBAIKAN STRUKTUR PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO DI DESA TANGEB, KECAMATAN MENGWI, KABUPATEN BADUNG, BALI - I Gusti Ngurah Putu Dharmayasa; I Komang Agus Ariana (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT Electricity supply is very important to improve people's lives. In Indonesia electricity is mostly generated by PLN as the state company that provide electricity for the entire people of Indonesia. PLN’s load is very high to provide electricity and to reduce the load of PLN, the potential of the electricity source should be utilized. One of the locations that have been built and used for micro-hydro power plant is the irrigation canal in the Tangeb village, Mengwi, Badung, Bali. Since it was built in 2014, micro-hydro power plant is expected to be used to provide electricity to the Pura Dalem within 100 meters from the power plant site, but can not function as expected because some parts of the structure were damaged, particularly on the foundation. In order for micro-hydro power plants can be used there should be analysis of the feasibility of existing structures. The research process begins with a review of the research sites, further soil sampling and ground testing in the field. The soil samples were tested in the laboratory. The test results of soil samples in the laboratory and field testing is used to calculate the carrying capacity of the land. The results of the soil bearing capacity were used to design the foundation. Analysis of the framework turbine is also conducted to determine whether the order turbines can still be used. Measurement of flow velocity is also performed to calculate the flow rate so that the electrical potential can be known. The results of the analysis of the feasibility of power plant micro-hydro in the Tangeb village obtained subgrade on the location of the turbine has a high bearing capacity that obtained the lowest allowable bearing capacity (qall) = 36.763 t/m2 based on test results in the laboratory, and the position of the hard soil in 1 meter depth. For steel frame buffer turbines, based on the results of the analysis with 9.7 ETABS program obtained that turbines are qualified or steel frame secure enough to support the movement of the turbine. The foundation of the turbine needs to be fixed with shallow foundation with a size of 0.95 m x 0.95 m, with a thickness 0.3 m and foundation depth of 1 meter. Reinforcement of foundation used for tension reinforcement φ 12 with a distance of 9 cm between the reinforcement and shrinkage reinforcement φ 12 with a distance of 18 cm. Potential electricity or power can be produced based on the calculation of the speed of the water, the water discharge resulting in low water level conditions is (W) = 3.3 kW. Keyword: micro-hydro, soil bearing capacity, foundation design